Optimalizace tvaru mazací mezery hydrodynamického ložiska s využitím umělých neuronových sítí - Kukla, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Práce se zabývá popisem hlavních částí turbodmychadla a vysvětlením pojmu optimalizace. Dále se práce zabývá popisem proudění skutečných kapalin a mazání u hydrodynamického ložiska. Je zde popsána tvorba výpočtového modelu, metamodelu a následné hledání globálního extrému. Konkrétně, při tvorbě metamodelů je použita technika neuronové sítě.

The thesis deals with the description of the main parts of the turbocharger and explains the concept of optimization. Furthermore, the work deals with the description of the flow of real fluids and lubrication of the hydrodynamic bearing. The work deals with the creation of a computational model, metamodel and subsequent search for a global extreme. In particular, the neural network metamodel technique is used in metamodel formation.
Lubricant gap shape optimization of the hydrodynamic thrust bearing using artificial neural networks
Keywords: Turbodmychadlo; optimalizace; axiální segmentové ložisko; metamodel; neuronová síť; Turbocharger; optimization; axial segment bearing; metamodel; neural network